2007
DOI: 10.1111/j.1472-765x.2006.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of optimal culture conditions for Gluconacetobacter hansenii cellulose production

Abstract: Aim:  The purpose of this study was to analyse the effects of different culture parameters on Gluconacetobacter hansenii (ATCC 10821) to determine which conditions provided optimum cellulose growth. Methods and Results:  Five culture factors were investigated: carbon source, addition of ethanol, inoculation ratio, pH and temperature. jmp Software (SAS, Cary, NC, USA) was used to design this experiment using a fractional factorial design. After 22 days of static culture, the cellulose produced by the bacteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…In the present study the combination of low pH of 4.0 and sucrose concentration of 10% proved to produce good nata. Hutchens et al (2007) confirmed that carbon source, ethanol addition and temperature are significant factors in the production of cellulose by Gluconacetobacter hansenii. Further the same authors noted different sugars produced optimal cellulose yields at different pH values.…”
Section: Resultssupporting
confidence: 73%
“…In the present study the combination of low pH of 4.0 and sucrose concentration of 10% proved to produce good nata. Hutchens et al (2007) confirmed that carbon source, ethanol addition and temperature are significant factors in the production of cellulose by Gluconacetobacter hansenii. Further the same authors noted different sugars produced optimal cellulose yields at different pH values.…”
Section: Resultssupporting
confidence: 73%
“…The productivity of BC depends on culture conditions, which include cultivation method, composition of growth medium (Keshk & Sameshima, 2005), dissolved oxygen (Kouda, Naritomi, Yano, & Yoshinaga, 1997), temperature, pH of the growth medium (Noro, Sugano, & Shoda, 2004), inoculation ratio (Hutchens, León, O'neill, & Evans, 2007) and inoculum age . The Plackett-Burman design and the response surface methodology (RSM) based on the Box-Behnken design can be used to optimize culture conditions (Plackett & Burman, 1946).…”
Section: Introductionmentioning
confidence: 99%
“…These include fruit juices (Kurosumi et al 2009), sugar cane molasses (Keshk and Sameshima 2006), sweet potato pulp (Shigematsu et al 2005), rotten apples (Gupta et al 2010), and maple syrup (Zeng et al 2011). The second factor is operating conditions such as dissolved oxygen (Kouda et al 1997), temperature, pH of the growth medium (Noro et al 2004), inoculation ratio (Hutchens et al 2007), and inoculum age. Both groups of factors must be at optimized levels to ensure optimum production of microbial cellulose.…”
Section: Introductionmentioning
confidence: 99%